Numerical and experimental investigations of hybrid nanofluids on pulsating heat pipe performance - Zufar M.; Gunnasegaran P.; Kumar H.M.; Ng K.C. (Elsevier Ltd, 2023)
Alumina; Aluminum oxide; Copper oxides; Evaporators; Heat pipes; Heat resistance; Heating; Silica; Slip forming; Thermal conductivity; Thermal conductivity of liquids; Two phase flow; Viscosity; Evaporator temperature; Experimental investigations; Nanofluids; Numerical results; Pulsating heat pipe; Stability measurements; Thermal Performance; Viscosity properties; Nanofluidics